T time: Emerging and new therapies for peripheral T-cell lymphoma. (March 2022) - Mina, Alain; Pro, Barbara
Abstract: Peripheral T-cell Lymphomas (PTCL) are a heterogenous group of aggressive non-Hodgkin lymphomas that are far less sensitive to chemotherapy than their B-cell counterparts. Despite their poor prognosis, they are treated similarly to most aggressive B-cell lymphomas, heavily relying on CHOP or CHOP-like combination chemotherapy irrespective of their different subtypes or biology. The last decade has seen the emergence of many targeted therapies that include histone deacetylase inhibitors, hypomethylating agents, monoclonal antibodies and PIK3 inhibitors, among others. However, prognosis remains poor especially in the relapsed/refractory setting. Using an extensive pubmed search, the authors will be summarizing the different trials that led to these approved targeted agents as well as novel combination strategies. The fundamental recognition that different subtypes of PTCL have specific biological features that drive not only proliferation, but also responses to different treatment approaches, should be informing the design of future clinical trials.